2018
DOI: 10.1093/jn/nxy079
|View full text |Cite
|
Sign up to set email alerts
|

Winter Cholecalciferol Supplementation at 51°N Has No Effect on Markers of Cardiometabolic Risk in Healthy Adolescents Aged 14–18 Years

Abstract: Supplementation with vitamin D3 at 10 and 20 μg/d, which increased serum 25(OH)D concentrations during the winter-time, had no effect on markers of cardiometabolic risk in healthy 14- to 18-y-old adolescents. This trial was registered at clinicaltrials.gov as NCT02150122.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 46 publications
4
16
1
Order By: Relevance
“…34,35 Overall, the GLM including the influence of measured 25(OH)D 3 start levels and the four SNPs This is consistent with the low to moderate vitamin D 3 supplement dose (5-20 µg per day) studies that tend to yield higher efficiency of treatment. [38][39][40]43,44 The 25(OH)D 3 end level in this study of 115 nmol L −1 is very similar to the plateau level found by Gallagher. At study end, there was an insignificant but mean increase of 6 nmol L −1 .…”
Section: Discussionsupporting
confidence: 89%
“…34,35 Overall, the GLM including the influence of measured 25(OH)D 3 start levels and the four SNPs This is consistent with the low to moderate vitamin D 3 supplement dose (5-20 µg per day) studies that tend to yield higher efficiency of treatment. [38][39][40]43,44 The 25(OH)D 3 end level in this study of 115 nmol L −1 is very similar to the plateau level found by Gallagher. At study end, there was an insignificant but mean increase of 6 nmol L −1 .…”
Section: Discussionsupporting
confidence: 89%
“…Inadequate vitamin D status was not an inclusion criterion only the study by Khayyatzadeh et al [27], although around 95% of the study population were either vitamin D deficient or insufficient. In four [28][29][30][31] out of the five included RCTs, mean baseline vitamin D was less than 50 nmol/L.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The articles included three non-randomized human interventions studies [25][26][27] and five controlled trials of vitamin D supplementation [28][29][30][31]. Three of the studies were conducted in the USA [25,26,29], two in Iran [27,30], one in Denmark [32], and one in each of Saudi Arabia [28] and the United Kingdom [31]. Participant age in the studies ranged from 4 to 18 years, and participant sample size ranged from 14 to 940.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of the vitamin D receptor by 1,25-dihydroxyvitamin D has also been proposed to affect blood pressure through a variety of mechanisms including involvement of the renin-angiotensin-aldosterone system and vascular smooth muscle (55,56) . Some randomised clinical trials in children and adolescents have indicated potential beneficial effects of vitamin D supplementation on TAG and glucose metabolism markers (12,57) , but most studies have not found any cardiometabolic benefits after an increase in serum concentration of 25(OH) D (9,58,59) . Our analyses were performed in healthy children with mean serum 25(OH)D > 50 nmol/l during autumn, when the serum 25(OH)D is expected to be close to the annual peak, as UVB radiation in Denmark is only sufficient to induce cutaneous vitamin D 3 synthesis from March to late September (60) .…”
Section: Discussionmentioning
confidence: 99%